1994
DOI: 10.1128/aac.38.2.356
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized amphotericin B-liposomes for treatment of systemic Candida infections in mice

Abstract: Mice lethally infected with Candida albicans were exposed to small-particle aerosols containing amphotericin B-liposomes. The drug, when administered twice daily for 2 h (0.58 mg/kg of body weight per day) on days 1, 2, and 3 postinoculation, significantly reduced the numbers of Candida organisms in the kidneys. Aerosol treatment increased the survival time of mice given 2 2-h treatments once a week for 4 weeks. A twice-weekly, 2-h small-particle aerosol administration of amphotericin B-liposomes for 1, 2, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A logical extension of this study, then, would be to administer an AmB-lipid-based formulation in this manner. Gilbert et al (72,73) did just that in experimental models of candidiasis and cryptococcosis. The treatment significantly reduced the number of Candida organisms in the kidneys and increased the mean time of survival and percent survival of mice.…”
Section: Other Therapeutic Approachesmentioning
confidence: 99%
“…A logical extension of this study, then, would be to administer an AmB-lipid-based formulation in this manner. Gilbert et al (72,73) did just that in experimental models of candidiasis and cryptococcosis. The treatment significantly reduced the number of Candida organisms in the kidneys and increased the mean time of survival and percent survival of mice.…”
Section: Other Therapeutic Approachesmentioning
confidence: 99%
“…In a following up study [53] , the rate of infection was 14 and 12% for the DC-AmB and AmBisome formulations, respectively. The lipid based formulations were well tolerated Amphotericin B Liposome [124] Liposome [125] Liposome [49] Liposome [126] Liposome [48] AmB-DC [52] AmBisome [44] AmBisome [127] AmBisome [46,47] AmB-Egg PC complex [128] Abelcet [129] Abelcet [130] Itraconazole Microparticles [55,56] with nausea, vomiting and taste dysfunction reported in only 3 of 381 patients [54] . The corresponding respiratory complications were also reduced or eliminated.…”
Section: Fungal Infections and Amphotericin Bmentioning
confidence: 99%
“…17,18 Dilauroylphosphatidylcholine (DLPC) aerosol formulations of beclomethasone and cyclosporin have already been administered in clinical settings. [31][32][33] Pharmacokinetic studies of liposome aerosols in mice with CPT showed high concentrations of CPT in the lungs, which were rapidly disseminated to the liver, tumor, brain, and other organs. 34 9-NC-DLPC liposome (LGNC) aerosols have demonstrated a favorable therapeutic index (significantly reduced tumor growth rate and shrinkage without serious side effects) in treating three different human cancer xenografts, breast, colon, and lung, in a nude mouse model.…”
Section: Aerosolized Administration Of Liposomal 9-nitrocamptothecinmentioning
confidence: 99%
“…Previous work has shown that certain drugs delivered to the respiratory tract in a liposome formulation may have advantages of noninvasive administration, including high pulmonary concentrations, often rapid entry into the systemic circulation, reduced toxicity, and reduced dosage requirements compared to oral and parenteral administration 17,18. Dilauroylphosphatidylcholine (DLPC) aerosol formulations of beclomethasone and cyclosporin have already been administered in clinical settings 31–33…”
Section: Aerosolized Administration Of Liposomal 9‐nitrocamptothecinmentioning
confidence: 99%